Infants’ Homes: Peculiarities of Spoken Language - Preikšaitienė, Audrė; Glebuvienė, Vitolda Sofija; Mazolevskienė, Aldona (Pedagogika, 2013)
When talking about the importance of education, M. Lukšienė emphasizes that in order to understand and master the process of education educators must be familiar with laws that dominate the world of an individual and his environment. The article presents the results of a spoken language analysis of children who grow in infants’ homes, in a specific environment of care and educational institutions for young children. It highlights some of the pragmatic, semantic, phonological and morphological characteristics of the children’s language. The article moreover presents linguistic self-expression levels and peculiarities of young children identified during the analysis of the corpus of language of children from specific environments and the possibilities of comprehending language elements and functions. Object of the research: expression of spoken language of children from infants’ home. The aim of the research is to analyze peculiarities of spoken language of children from infants’ home. Research methods: analysis of scientific literature on the peculiarities of children’s language use at an early age, empirical observation of a child, analysis of the peculiarities of spoken language (understanding and use), comparative empirical analysis, that allow for presenting educational statements relevant to the language of young children. Subjects of the research: 157 pupils from infants’ home. Research results: this research was an attempt to analyze spoken language data of young children from the Lithuanian infants’ homes obtained by means of observation only. The research of peculiarities of the speech of children from the infants’ homes on a phonological level revealed that the overall ability of young children to articulate sounds in the Lithuanian language is to be considered only satisfactory, inasmuch as only 4 out of 30 young children are able to pronounce nearly all the sounds and the speech of most of the children is distinguished by an abundance of phonemic errors: this means replacement of difficult – to - pronounce sounds with other sounds, omission, shortening of words, confusing sounds with similar articulation, extension, incorrect pronunciation of soft and hard phonemes, failure to pronounce and replacing vowels, monophthongization of diphthongs and diphthongization of a long mid vowel “ė”, errors in shifting from one sound to another, distortion of sound / syllabic word structure, etc. The research of grammar (morphology) of speech of children from the infants’ homes led to the conclusion that children from the infants’ homes do not know or confuse generalizing terms, do not know their individual names. Thy moreover have little knowledge of colors. These children use one verb to identify similar actions. Nouns in the speech of children from the infants’ homes usually are names of clothing, body parts and performers of actions. Children communicate using words with a constant meaning, understand some of the grammatical forms; however, they sometimes fail to identify the quantity of nouns and prefer singular form. There are almost no adjectives in an independent speech. Children make errors when using verb forms, for example, use infinitive form instead of one of the other forms. In addition to names of objects, actions and properties, uninflected parts of speech occur: prepositions, adverbs, conjunctions, etc. Children also differentiate between interrogatives. Children from the infants’ homes are already able to answer questions, while looking at pictures. However, they do not understand consistent patterns of direct control and intensely confuse declensional forms with each other. They skip, interchange prepositions and pronounce them inaccurately.